Hesitation Pause as One of the Basic Characteristics of Spontaneous Speech - Анусас, Пятрас (Kalbotyra, 1985)
Interdisciplinary investigation of spontaneous speech has given rise to a new approach towards spoken language analysis, i. e. speechology. When utterances are organised at the time of speaking they emerge haltingly, interspersed with filled and silent (unfilled) pauses. This intermittent quality of spontaneous, i. e. unrehearsed speech has attracted many investigators both linguists and non linguists seeking to understand the decision making process underlying speech production. In the present paper, the literature bearing on hesitation pauses in spontaneous speech has been reviewed to evaluate the interdisciplinary explanation of hesitation phenomena, i. e. to what degree findings of psychological and psycholinguistic studies are applicable to linguistic theories. The first aim of the study has been to describe functions (cognitive and linguistic) that hesitation pauses were thought to reflect .